2018
DOI: 10.3168/jds.2018-14770
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ad libitum or restricted access to total mixed ration with supplemental long hay on production, intake, and rumination

Abstract: Limiting feeding time has been a concept used in growing and nonlactating ruminant animals with good success, especially in improving feed efficiency while maintaining normal rumen function and fiber digestibility. This study evaluated the physiological and productive responses of cows fed a total mixed ration (TMR) available for 24 or 19 h/d with or without access to additional long hay. Eight multiparous Holstein cows were used in a replicated 4 × 4 Latin square design with 21-d periods. Rations were formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 27 publications
8
21
0
Order By: Relevance
“…The experimental diets were balanced thanks to an adjustment of the corn flakes and grass hay proportions among the treatments, thus no substantial changes were observed in chemical composition and theoretical supply of ME and MP. TMRs were lower in particle size than usually recommended (Heinrichs 2013), but in accordance with previous trial (Fustini et al 2017, Cavallini et al 2018 and similar to those observed in several commercial farms of PR area (Fustini et al 2016). This level of dietary particle size minimised the risk of cows sorting (Fustini et al 2016).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The experimental diets were balanced thanks to an adjustment of the corn flakes and grass hay proportions among the treatments, thus no substantial changes were observed in chemical composition and theoretical supply of ME and MP. TMRs were lower in particle size than usually recommended (Heinrichs 2013), but in accordance with previous trial (Fustini et al 2017, Cavallini et al 2018 and similar to those observed in several commercial farms of PR area (Fustini et al 2016). This level of dietary particle size minimised the risk of cows sorting (Fustini et al 2016).…”
Section: Discussionsupporting
confidence: 89%
“…This level of dietary particle size minimised the risk of cows sorting (Fustini et al 2016). Feed and water intake were similar to those observed in previous studies conducted under the same experimental conditions (Cavallini et al 2018).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, environmental conditions and forage and feed types may negate the effect of low rumen pH on feed preference (Cooper et al, 2002;Salfer et al, 2018). Cavallini et al (2018) evaluated the physiological and production responses of cows that were fed a TMR for 19 or 24 h with or without supplemental long dry hay to improve the feed efficiency of the limit-fed diet. Few production differences were observed once cows adapted to diet feeding regimens.…”
mentioning
confidence: 99%
“…These authors explained this observation by changes in the dam: calf ratios that reduce rumen capacity and increase calving pain (Stanley et al, 1993;Proudfoot et al, 2009), preventing animals from feeding and ruminating. Rumination time is influenced by several factors: adequate physically effective NDF in the diet (Mertens, 1997), forage inclusion and composition (Fustini et al, 2011), and diurnal feed availability (Cavallini et al, 2018). Moreover, health disorders, pain, and distress may inhibit rumination; indeed, a decrease in RT is considered a reliable indicator of stress and disease (Soriani et al, 2012;Calamari et al, 2014;Schirmann et al, 2016).…”
Section: Discussionmentioning
confidence: 99%